THE CHILDBIRTH SERVICES ASPECT THAT INFLUENCE PATIENT SATISFACTION - Anggraheny, Hema Dewi; Sudiro, Sudiro (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Pregnant women have higher expectations of the care providers attitude in order to have childbirth satisfaction. This study aims to analyze the relationship between childbirth services and birth satisfaction in Roemani Muhammadiyah Semarang hospital. We used a cross sectional design and used an interview to collect the data, it was conducted from July to August 2016. A total of 79 women were enrolled in the study that fulfill the inclusion and exclusion criteria. The childbirth services and patient satisfaction were measured using survey instruments which weâ€™d measured the reliability and validity previously. The linier regression were applied. The majority of the patients (94,9%) were 21-40 years old, 67,1% were university graduate, 40,5% were housewife, 62% were multigravida, and Â 57% were delivered by cesarean section. There were significant effect between interpersonal relationship (p=0,0001), patient decision choice (p=0,001), and breastfeeding management (p=0,021) and birth satisfaction. The strongest predictor of birth satisfaction was interpersonal relationship.